Análisis de los anglicismos informáticos crudos del léxico disponible de los estudiantes universitarios de traducción - Bolaños-Medina, Alicia (2010)
Most technical terms in the field of Computer Science are Englishloanwords. English words are frequently preferred to Spanish terms because of different reasons, for instance, because of linguistic economy. Inthis paper, we reveal the results of an empirical study about the frequencyof use of pure anglicisms. It has been carried out among students ofTranslating and Interpreting at the University of Las Palmas de GranCanaria (Spain). The scope of use of lexical anglicisms by individuals in theanalysed sample seems to be relatively high, but slightly lower than thatof Computer Science students who participated in another preliminarypartial study. Those students who provided more words for definitionsalso suggested more synonyms for the terms, and also used more Englishterms.